TAX AVOIDANCE, AUDIT FIRM AND COST OF DEBT: DOES INTEGRATED REPORT HAVE A PROMINENT ROLE? - Rasyidah, Hana Lathifa; Fitriana, Vita Elisa (Universitas Multimedia Nusantara, 2024)
Abstract— This research aims to investigate the influence of tax avoidance, audit firm to cost of debt with integrated report as moderating variable in mining listed company in Indonesia Stock Exchange (IDX). Mining companies was selected due to the high rate of the borrowing cost of mining company from domestic and foreign bank. The sample was obtained using purposive sampling method with observation periods for 4 consecutive years (2019-2022). Moderated Regression Analysis (MRA) is used as an analytical model in this study. The empirical results showed that tax avoidance will increasing cost of debt, while audit firm is reducing it. Integrated report reveals two different results, where it is able to moderate the relationship between tax avoidance and cost of debt but unable to moderate audit firm and cost of debt. This result shed the light of the importance for company which has tax avoidance policy for doing voluntarily integrated report since it able to reduce the cost of debt. Besides, if the company has assigned big for auditor, the integrated reported does not provide either advantage or disadvantage impact. Keywords: Tax Avoidance; Audit Firm; Cost of Debt; Integrated Report